Glial Cells Promote Myelin Formation and Elimination - Hughes, Alexandria N. (Frontiers in Cell and Developmental Biology, 2021)
Building a functional nervous system requires the coordinated actions of many glial cells. In the vertebrate central nervous system, oligodendrocytes myelinate neuronal axons to increase conduction velocity and provide trophic support. Myelination can be modified by local signaling at the axon-myelin interface, potentially adapting sheaths to support the metabolic needs and physiology of individual neurons. However, neurons and oligodendrocytes are not wholly responsible for crafting the myelination patterns seen in vivo. Other cell types of the CNS, including microglia and astrocytes, cultivate the myelin garden. In this review, I cover the contributions of non-neuronal, non-oligodendrocyte cells to the formation, maintenance, and pruning of myelin sheaths. I address ways that these cell types interact with the oligodendrocyte lineage throughout development to modify myelination. Additionally, I discuss mechanisms by which these cells may indirectly tune myelination by regulating neuronal activity. Understanding how glial-glial interactions regulate myelination is essential for understanding how the brain functions as a whole and for developing strategies to repair myelin in disease.